Assessment and diagnosis of individuals with Autism Spectrum Disorder (ASD) - Wolf, Julie M. (Henry Stewart Talks, 2020)
Description of ASD assessment and reasons for referral, Achievement testing, Neuropsychological assessment, Medical evaluation, Diagnostic formulation, Assessing co-morbidities, Differential diagnosis, Treatment recommendations informed by assessment